Respons Pembaca Novel ‘Āid ilā Ḥaifā Karya Ghassan Kanafani Pada Aplikasi Abjjad: Kajian Resepsi Sastra Diakronis - Ulum, Muhammad Bachrul; R.A.G, Mohamad Sulthan Lingga (Fakultas Adab dan Humaniora UIN Sunan Ampel Surabaya, 2025)
This study investigates readers’ responses to ‘Āid ilā Ḥaifā by Ghassan Kanafani on the Abjjad application, employing a diachronic literary reception approach. The research aims to explore how contemporary digital readers interpret the novel across time and how their responses reflect aesthetic, emotional, and ideological dimensions. This study adopts a qualitative descriptive method within the framework of literary reception theory. The data consist of readers’ comments and ratings collected from the Abjjad platform, focusing on the top 40 comments with the highest engagement over approximately a decade (2013–2023). Data were collected using non-participatory observation and note-taking techniques, then analyzed to identify patterns of reception related to plot, language style, and political ideology. The findings reveal that readers’ reception is predominantly shaped by three main aspects. First, the plot is perceived as emotionally powerful, particularly due to its delayed climax and narrative shock, which intensify readers’ engagement. Second, Kanafani’s language style is widely appreciated for its simplicity, expressiveness, and immersive quality, enabling readers to experience the narrative vividly. Third, in terms of political ideology, most readers tend to support militant resistance as the primary means of liberation, although alternative perspectives emphasizing critical awareness and non-violent resistance also emerge. This study demonstrates that digital literary platforms such as Abjjad function as dynamic spaces for meaning-making, where readers actively negotiate aesthetic and ideological interpretations. It also highlights the transformation of literary reception in the digital era, where readers are not merely passive consumers but active producers of meaning.